Narrazioni ibride post-sovietiche Per una letteratura ucraina di lingua russa - Puleri, Marco (Premio Ricerca «Città di Firenze», 2016)
In light of the dramatic events which have been shocking Ukraine since November 2013, this work's itinerary aims at functioning as a basis for the formulation of new contact points, for a dialogue between traditions and cultures which nowadays are again being shaken by the events of history. The author examines the self-identification paths of the literary phenomenon of Russian language in Ukraine. With the help of interviews with important representatives of the Ukrainian Russian-speaking literary scene, made on the eve of the so-called 'Ukrainian crisis', the author shall closely observe the origins of the marginal nature of these 'post-Soviet hybrid narratives'.